2022
DOI: 10.3389/fnut.2022.917043
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Interact With Lipids Metabolism and Affect Gut Health

Abstract: Probiotics have attracted much attention due to their ability to modulate host intestinal microbe, participate in nutrient metabolism or immunomodulatory. Both inflammatory bowel disease (IBD) and bowel cancer are digestive system disease, which have become a global public health problem due to their unclear etiology, difficult to cure, and repeated attacks. Disturbed gut microbiota and abnormal lipid metabolism would increase the risk of intestinal inflammation. However, the link between lipid metabolism, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 109 publications
(134 reference statements)
0
18
0
Order By: Relevance
“…In the gut, bile acids are involved in lipid transport and can affect the condition of the body by modulating the gut microbiota. 38 RA upregulated the level of chenodeoxycholic acid 3-sulfate, sulfolithocholylglycine, 3a,6b,7b-Trihydroxy-5b-cholanoic acid and nutriacholic acid. Coincidentally, evidence has shown that chenodeoxycholic acid reduces liver damage by regulating inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…In the gut, bile acids are involved in lipid transport and can affect the condition of the body by modulating the gut microbiota. 38 RA upregulated the level of chenodeoxycholic acid 3-sulfate, sulfolithocholylglycine, 3a,6b,7b-Trihydroxy-5b-cholanoic acid and nutriacholic acid. Coincidentally, evidence has shown that chenodeoxycholic acid reduces liver damage by regulating inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…Linoleic acid is a polyunsaturated fatty acid that cannot be synthesized in the body and must be obtained from dietary sources ( 36 ). It has been reported that linoleic alcohol is related to atherosclerosis and inflammatory diseases, being a main component of the cell plasma membrane and a precursor to fatty acids such as prostaglandins and leukotrienes ( 37 ). In general, the decreased level of unsaturated fatty acids observed in this study indicated that a long-term high-fat diet might lead to hyperlipidemia, altered fatty acid metabolism, and oxidative stress reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Their classification into pro-inflammatory (PGE 2 , PGE 3 , LTB 4 , and LTB 5 ) and pro-resolutive (RvD1 and LxA4) mediators ( 38 ) is insufficient to explain their roles in the intestine ( 51 ), especially considering that 3-hydroxylated long-chain fatty acids (C12-, C14-, C16-, and C18-3OH) can be produced by bacteria and protect against colitis ( 52 ). The impact of these oxylipins on IBD could be greater than expected, as they can be regulated by diet and/or induce microbiota changes ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%